Land Use and Water Quality Along a Mekong Tributary in Northern Lao P.D.R. - Ribolzi, Olivier; Cuny, Juliette; Sengsoulichanh, Phonexay; Mousques, Claire; Soulileuth, Bounsamai; Pierret, Alain; Huon, S.; Sengtaheuanghoung, Oloth (Springer, 2011)
Improving access to clean water has the potential to make a major contribution toward poverty reduction in rural communities of Lao P.D.R. This study focuses on stream water quality along a Mekong basin tributary, the Houay Xon that flows within a mountainous, mosaic land-use catchment of northern Lao P.D.R. To compare direct water quality measurements to the perception of water quality within the riparian population, our survey included interviews of villagers. Water quality was found to vary greatly depending on the location along the stream. Overall, it reflected the balance between the stream self-cleaning potential and human pressure on the riparian zone: (i) high bacteria and suspended load levels occurred where livestock are left to free-range within the riparian zone; (ii) very low oxygen content and high bacteriological contamination prevailed downstream from villages; (iii) high concentrations of bacteria were consistently observed along urbanized banks; (iv) low oxygen content were associated with the discharge of organic-rich wastewater from a small industrial plant; (v) very high suspended load and bacteria levels occurred during flood events due to soil erosion from steep cultivated hill slopes. Besides these human induced pollutions we also noted spontaneous enrichments in metals in wetland areas fed by dysoxic groundwater. These biophysical measurements were in agreement with the opinions expressed by the majority of the interviewees who reported poor and decreasing water quality in the Houay Xon catchment. Based on our survey, we propose recommendations to improve or maintain stream water quality in the uplands of northern Lao P.D.R.